Repeat ridge jumps and microcontinent separation: insights from NE Arabian Sea. (January 2015) - Misra, Achyuta Ayan; Sinha, Neeraj; Mukherjee, Soumyajit
Abstract: Microcontinents separate due to ridge jumps associate either asymmetric sea floor spreading or plume–ridge interactions. India separated from Seychelles at ∼64 Ma by asymmetric sea floor spreading initially when the spreading centre in the Mascarene Basin jumped towards the Indian sub-continent between magnetic chrons C29 and C28. The subsequent tectonics is difficult to comprehend since Laxmi Ridge-another microcontinent-formed during the later phase. Most of the studies considered the Laxmi Ridge as a sliver. Others considered it to be oceanic crust. High resolution, deep (∼25 km) seismic data reveals that ( i ) the ridge possesses > 15 km deep sea-ward dipping reflector (SDR) packages; ( ii ) normal faulted rift valleys devoid of syn-rift sedimentary packages; and ( iii ) axial magma chambers 5–7 km beneath the ridge top. Additionally, from 2D forward gravity models we deduce that the ridge most possibly comprises of high density (oceanic) crust. We conclude the Laxmi Ridge to be indeed composed of oceanic crust and a fossil spreading centre. We thus identified the ridge jumps and their relation to the Seychelles microcontinent separation. Previous numerical models suggest that the time required for a ridge jump is controlled by magmatic heating, spreading rate at the ridge, and plate ages. For repeated ridge jumps, the additional factor is the dynamic relation between the plume and lithosphere in terms of melt transfer and heating. We find that the medium spreading rates and high magmatic heating due to the Réunion plume and young plates favoured rapid and repeated ridge jumps towards the plume.